Multi-Actor Innovation in Child-Friendly City Policy - Handam Handam; Randi Akbar (Journal La Bisecoman, 2020)
This article describes the policy of a Child-Friendly City, Actors, and agency and presents the Multi-Actor Innovation point of view that colors the child-friendly city policy. The Child-Friendly Regency/City Policy places a child-friendly city as a prerequisite to ensure that children grow and develop properly, have their rights protected, and their physical and psychological needs are met. Apart from being supported by the Ministry of Women's Empowerment and Child Protection, APSAI is also supported by child protection organizations, such as UNICEF, Save The Children. Various actors who are interested in contributing to a child-friendly city can participate. Multi-Actor Innovation can only occur if the collaboration that is established provides space for each actor who has different roles to be given the freedom to innovate based on their respective roles. The aim of the Multi-Actor Innovation is to offer better social learning analysis by integrating insights from sustainability science and social learning science traditions.